Inflammation Modulation With Methanol Zea Mays Cob Husk On An Experimental Model In Albino Rats - Dominguez Montero, Genny; Mpewo, Thadeus Judah; Betancourt Valladares, Miriela; Cadenas Freixas, José Luis; Mirabal Nápoles, Marjories (Revista Cubana de Investigaciones Biomédicas, 2019)
Background: Several parts of Zea mays (maize) have been used for the treatment of several ailments including inflammatory conditions. Objective: to evaluate the modulatory effect on carrageenan-induced inflammation of the methanol extract of Zea mays cob husk in Albino rats. Methods: 9.45% maize cob husks methanol extract was obtained by soxhlet extraction and the phytochemical screening was done. The carrageenan-induced paw edema model of acute inflammation was carried out to 30 Albino rats which were divided into five groups, two controls (negative and positive) and three experimental. A single oral methanol extract (100, 200 or 400mg/Kg) were administered to the experimental groups. Indomethacin 10mg/Kg was used as positive control. The paw volume up to the tribiotural articulation was measured at 0, 1, 3 and 6th hours. Inflammation was expressed as an increase in paw volume due to carrageenan injection and the percentage inhibition produced by the extracts was calculated to assess the anti-inflammatory activity. Acute toxicity study was conducted. ANOVA test was applied and P value less than 0.05 were considered significant. Results: saponins, tannins and polyphenols were present in the plant extract. Doses below 5000mg/Kg were considered safe. Significant anti-inflammatory activity was shown at 400mg/Kg after sixth hours. Conclusions: The anti-inflammatory effect of Zea mays cob husk extract may be attributed to the presence of saponins, tannins and polyphenols. Percentage inhibition of inflammation by the extracts showed dose and time dependence. The anti-inflammatory effect was found significant for safe concentrations of the plant extract.